Detection and evaluation of fraud during the public sector audit - Sokolenko, L. F. (Statistics of Ukraine, 2022)
The activities of public sector institutions are an area, which is sensitive to the fraud risks. This is due to the significant use of budget funding, the existence and access to state property. Fraud and corruption are serious threats to the functioning of the public sector because of the potential financial and reputation damage and consequences from fraud for the institution. The application of international standards and best practices of public sector audit will allow to detect and prevent cases of fraud. It will help to save budget funds and state property. The research is based on the results of scientific works of domestic and foreign scientists, texts of international auditing standards on public sector audit (ISSAI) and national regulations of Ukraine. The study used cases of fraud with budget funds basing the information from the reports of the Accounting Chamber of Ukraine for 2018-2021. Therefore, there may be no direct visible evidence of fraud, and the auditor should pay attention to identifying fraud risks, including third parties’ testimonials, to consider the results of previous public audits, to provide interviews with management and employees of organization. The general procedure for detecting fraud during a public sector audit is determined in paper. It includes the range of steps, that should be done by public sector auditor: fraud risk assessment at the audit planning stage; identification of transactions for which audit procedures should be performed; audit evidence gathering, assessment of their sufficiency and acceptability and conducting additional procedures (if necessary); consideration of audit evidence and the formation of an opinion on the existence of fraud facts; communication on the information to those who are endowed with the highest authority at the object of audit; consideration of competent authorities to be informed of the existence of fraud at the object of audit. This will help to structure the audit work during the public sector audit and to determine the logic of the auditing process based on the assessed risks of fraud, and to achieve results of auditor procedures, that could be evaluated.